Hemorrhagic toxins from rattlesnake (Crotalus atrox) venom. Pathogenesis of hemorrhage induced by three purified toxins. - Ownby, C. L. (1978)
The pathogenesis of hemorrhage induced by three purified components of rattlesnake (Crotalus atrox) venom was studied at the light and electron microscopic levels. Crude venom was fractionated by anion exchange and gel filtration in four steps. beta-Alanine acetate disk gel electrophoresis was used to demonstrate electrophoretic homogeneity. White mice were injected intramuscularly with 0.1 ml of a sublethal dose of hemorrhagic toxin. Gross examination revealed extensive hemorrhage 5 minutes after the injection of hemorrhagic toxins alpha and episilon; the same amount of hemorrhage was not present until 3 hours after the injection of hemorrhagic toxin beta. Light microscopic examination of muscel after injection of the toxins revealed areas of extensive hemorrhage in which very few intact capillaries could be found and also adjacent areas of slight hemorrhage in which capillaries were in various stages of degeneration. Necrosis of muscle cells was evident in tissue injected with hemorrhagic toxin beta. Electron microscopic examination showed that capillaries from toxin-injected muscle were in various stages of degeneration. Endothelial cells became very thin and broke down into vesicles prior to complete rupture. Gaps were formed within the cells while intercellular junctions remained intact. Plasma and erythrocytes leaked through these gaps and were observed in the endomysium. Many gaps were plugged with platelet aggregations. Collagen and the basal lamina associated with capillaries were usually disorganized or absent. The experimental injection of three purified hemorrhagic toxins induced hemorrhage by the same mechanism as does the crude venom, ie, per rhexis. In addition, one of the toxins, hemorrhagic toxin beta, causes myonecrosis.